(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
According to a 2017 Ministry of Health study, Saudi Arabia’s healthcare industry has had remarkable growth over the past several years, employing 423,940 people in the medical field. Value-based healthcare is being approached by the healthcare industry through a significant transition brought about by the adoption of the Kingdom’s Vision 2030. New obstacles accompany the shift. Effective workforce planning, a careful balancing act between the science of analysis and the art of execution, is a necessary first step in achieving long-term objectives. Academic and practical discourse has dominated conversations about employee performance and leadership dynamics in Saudi Arabia’s rapidly evolving healthcare industry. These healthcare organizations are addressing global technological advances and the demands of pandemic readiness in addition to unique mixes of operational, cultural, and creative challenges. A leader’s behaviour takes several forms while they are in a leadership role. Determining the effect of professional seniority on the performance of health cadres in the Saudi healthcare system was the goal of this study.